Virtual Reality in Astronomical Education: Improving the Understanding of Eclipses with Interactive Simulations - Carneiro, Ana Cesarina de Oliveira; Paillard, Gabriel Antoine Louis; Araújo Neto, João Batista de; Vidal, Creto Augusto; Cavalcante Neto, Joaquim Bento; Leite Junior, Antonio José Melo; Gomes, George Allan Menezes (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
The teaching of astronomical concepts, such as eclipses, faces challenges due to their complexity and the difficulty of spatial visualization. This research proposes the use of Virtual Reality (VR) to enhance the understanding of these phenomena. An immersive virtual environment was developed, allowing users to explore accurate simulations of solar eclipses. The approach involves the customization of celestial models, integration into a VR editor (Universal), and execution of the simulations on HMDs (Universal Runner). The paper also discusses future advancements, such as the inclusion of new scenarios and the automation of experiences, aiming to improve interactive learning.